A NEW FORMULATION INHIBITS EGG HATCHING AND REPELS MOSQUITO OVIPOSITION AT BREEDING SITES, CONTRIBUTING TO THE CONTROL OF DENGUE VECTOR (Vietnam Journal of Community Medicine, 2022)
Anacardium occidentale is a typical plant species in tropical countries, including Vietnam. Its nut shell extracts possess biological effects, such as larviciding. Solvent extracts of the nut shell of this plant were reported to contain 62.9% anacardic acid (AA). However, AA is a liquid mixture of four compounds, differentiating by the hydrophobicity of side chains, making it water-insoluble. In this study, we aim to overcome this drawback by converting AA into a sodium salt, which exists in anionic condition, and then combine with ethanol extract of lime peel to create a new pellet product (MCA) to evaluate the ovicidal and repellent activities against Aedes mosquitoes at their breeding grounds. The results showed that the efficiency of yielding salt form from the AA liquid extract was 96%, which was then mixed with lime peel extract and additives at a 2 : 1 : 7 ratio to produce MCA pellets. The formulation demonstrated egg hatch inhibition upon Ae. aegypti (82.9%) and Ae. albopictus (90.6%) at 50 ppm, compared to the negative control (P0.05). Similarly, at the same concentration, MCA exhibited 68.5% and 78.1% repellent activities toward Ae. albopictus and Ae. aegypti from the breeding site, respectively, which differed significantly (P
Keywords: Anacardium occidentale, MCA formulation, oviposition deterrence, ovicidal activity.